PERAN PARTAI ACEH UNTUK MEMBERIKAN PENDIDIKAN POLITIK KEPADA MASYARAKAT DI KOTA LANGSA - Mohammad Shadiqie Alfarizi; Harun H; Hamdani h (Fakultas Hukum Universitas Malikussaleh, 2021)
This study aims to determine and analyze the role of the Aceh Party in providing political education to the people in Langsa City, the obstacles that make it difficult for the Aceh Party to provide political education and the efforts made by the Aceh Party to provide political education to all levels of society. Based on article 79(a) No. 11 of 2006 of the Law on the Government of Aceh states that local political parties function as a means of political education for members and the community. The Aceh Party in Langsa City has not been maximal in providing political education to all people in the Langsa City area. This can be seen from the lack of public understanding of political education as well as knowledge of the rights and obligations of the community in political education. This is because the Aceh Party in Langsa City still prioritizes political education for its cadres and the Aceh Party's